Legal Analysis Regarding Efforts to Annul the Decision Arbitration in District Court - Hairul Anam; Atisa; Naziera Al Hadar; Rahma Seliati Br Sitorus; Tasya Alifiya (ISNU Nine-Star Multidisciplinary Journal, 2025)
Arbitration is an alternative dispute resolution outside the court (non-litigation) that is final and binding on the parties. However, in practice, arbitration decisions can still be annulled at the District Court based on certain reasons stipulated in the law. This study aims to analyze the legal basis, procedures, and considerations of judges in deciding on requests to annul arbitration decisions at the District Court. The research method used is a normative legal approach with secondary data sources in the form of laws and regulations, court decisions, and related legal literature. The results of the study indicate that efforts to annul arbitration decisions are regulated in Article 70 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, which requires the presence of certain elements such as alleged forged documents, concealment of important documents, or decisions based on deception. In addition, annulment can only be submitted within a maximum period of 30 days after the decision is received. The District Court's decision on an annulment request is final, but it still leaves room for legal uncertainty and inconsistent application of norms by judges. Therefore, there is a need for a strengthened legal system and more consistent standards of interpretation in the annulment process for arbitration awards.